Primer informe de virus infectando pitaya en Argentina - Cabrera Mederos, Dariel; Jaramillo, M.M.; Ortiz, Claudio Manuel; Flores, Ceferino Rene; Silva, Milagros Itatí; Trucco, Veronica Milagros; Nome Docampo, Claudia; Fernandez, Franco Daniel; Badaracco, Alejandra; Nahirñak, Vanesa; Castellano Collazo, Onias; Portal, O.; et al. (Asociación Argentina de Fitopatólogos (AAF), 2025)
Poster y resumen